Association of a reduction in low-density lipoprotein cholesterol with incident cardiovascular and cerebrovascular events among people with type 2 diabetes mellitus. (29th August 2020) - Li, Lin; Ambegaonkar, Baishali M; Reckless, John PD; Jick, Susan
Abstract: Background: Although there is overwhelming evidence that reducing low-density lipoprotein cholesterol (LDL-C) with statins leads to reductions in cardiovascular disease, less is known about the effects in persons with type 2 diabetes mellitus (T2DM) without pre-existing vascular events. Methods and results: Using the UK-based General Practice Research Database we conducted a retrospective cohort study of 21, 998 T2DM patients aged 35–69 with ≥2 prescriptions for lipid-modifying therapy (2000–2009). We categorized LDL-C change (mmol/l) between last available and baseline lipid values as reduction (≥3.0, 2.0–2.9, 1.0–1.9, 0.3–0.9), no-change (±0.2 of baseline), or increase (>0.2). Outcomes were incident composite cardiovascular ( n  = 621) and cerebrovascular events ( n  = 274). We estimated hazard ratios (HRs) of study outcomes and 95% confidence intervals (CIs) for LDL-C change compared with the no-change group. Compared to no changes, adjusted HRs of cardiovascular events for a reduction ≥3.0 and a reduction between 2.0–2.9 were 0.41 (95% CI: 0.23–0.71) and 0.51 (95% CI: 0.34–0.76) ( p for linear trend <0.001). LDL-C reduction yielded a decreased cerebrovascular event risk compared to no change, even with the smallest reduction (adjusted HR = 0.59, 95% CI: 0.36–0.98). Conclusions: Decreasing LDL-C is associated with a reduced risk of cardiovascular and cerebrovascular events among T2DM patients without such pre-existing events. The magnitude of the protective effect on cerebrovascular events is less certain, and further studies are warranted.